2022
DOI: 10.3389/fmicb.2022.1000526
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect and mechanism of action of juniper essential oil on gray mold in cherry tomatoes

Abstract: Juniper essential oil (JEO), which is mostly known as an immune system booster and effective detoxifier, has substantial antimicrobial activity. A comparison of the inhibitory effects of three plant essential oils from juniper (Juniperus rigida), cedarwood (Juniperus virginiana), and cypress (Crupressus sempervirens) on four plant pathogenic fungi indicated that JEO was the most effective at inhibiting the growth of gray mold (Botrytis cinerea). Additional studies were subsequently conducted to explore the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The observation from this study is consistent with literature on the response of B. cinerea to EOs and other botanical fungicides ( Yang et al, 2020a ; Wu et al, 2022 ). For instance, Yang et al (2020a) demonstrated that treatment of B. cinerea with cembratrien-diols induced oxidative stress, which resulted in injured membrane system with a significant reduction of H 2 O 2 content in the mycelia.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The observation from this study is consistent with literature on the response of B. cinerea to EOs and other botanical fungicides ( Yang et al, 2020a ; Wu et al, 2022 ). For instance, Yang et al (2020a) demonstrated that treatment of B. cinerea with cembratrien-diols induced oxidative stress, which resulted in injured membrane system with a significant reduction of H 2 O 2 content in the mycelia.…”
Section: Resultssupporting
confidence: 92%
“…For instance, Yang et al (2020a) demonstrated that treatment of B. cinerea with cembratrien-diols induced oxidative stress, which resulted in injured membrane system with a significant reduction of H 2 O 2 content in the mycelia. Similarly, H 2 O 2 content was found to be significantly lower in B. cinerea mycelia exposed to juniper EO compared to the untreated control during 12 h incubation period ( Wu et al, 2022 ). The balance between reactive oxygen species (ROS) production and scavenging capacity is crucial for any typical cellular processes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…MDA is one of the major markers for the peroxidation of membrane lipids and the damage degree of the cell membrane . The contents of MDA in U.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma membrane acts as a barrier to protect the cell by regulating the exchange of compounds inside and outside of the cell and maintaining homeostasis of the intracellular environment. 18 The effect on the plasma membrane has been reported as one of the major action mechanisms of antifungal agents present in methyl thujate on Botrytis cinerea, 16 tea tree oil on Monilinia fructicola, 17 and linalool and pinosylvin monomethyl ether on Aspergillus flavus. 19,20 To evaluate the effects of 2,4-DTBP on the membrane integrity of U. virens, PI staining was performed with mycelia cultured in PSB medium with or without 2,4-DTBP.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%